Analisis Trend dan Kontribusi Sektor Pertanian pada Produk Domestik Regional Bruto Provinsi Sulawesi Barat - Aryanti, Wulan; Ekowati, Titik; Mukson, Mukson (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aimed to 1). analyze the trend of Gross Regional Domestic Product (GRDP) in the agricultural sector of West Sulawesi, 2). analyze the contribution of each agricultural subsector to the formation of GRDP in the agricultural sector of West Sulawesi, 3). analyze the contribution of each district to the formation of GRDP in the agricultural sector of West Sulawesi during of 2014-2023. This study was carried out in 1st-14th January 2025 using secondary data for research methods. The data used in this study is the time series data of GRDP in the agricultural sector of West Sulawesi during 2014-2023 sourced from the publications of the Badan Pusat Statistik (BPS). The data analysis method used to analyze the first purpose is the least squares method. Meanwhile, to analyze the second and third purpose, the calculation contribution between the total GRDP of each district or the total GRDP of agricultural subsector and the total GRDP of the agricultural sector of West Sulawesi during 2014-2023. The results of the study show the increasing GRDP in the agricultural sector for each year. Some potential subsectors or those with low contributions require alternative strategies such as agricultural modernization, agricultural intensification, and agricultural diversification.